2015
DOI: 10.1021/acs.jpcc.5b02121
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Adhesion with Polyelectrolyte Brushes Tailored via the Uptake and Release of Trivalent Lanthanum Ions

Abstract: Applications of end-tethered polyelectrolyte "brushes" to modify solid surfaces have been developed and studied for their colloidal stabilization and high lubrication properties. Current efforts have expanded into biological realms and stimuli-responsive materials. Our work explores responsive and reversible aspects of polyelectrolyte brush behavior when polyelectrolyte chains interact with oppositely charged multivalent ions and complexes, which act as counterions. There is a significant void in the polyelect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 43 publications
(116 reference statements)
6
57
1
Order By: Relevance
“…), even at very low concentration, can cause abrupt collapse of sparsely tethered PSS brushes [26,27]. Our NR results demonstrate that this conclusion also holds for densely tethered PSS brushes.…”
Section: +supporting
confidence: 67%
See 2 more Smart Citations
“…), even at very low concentration, can cause abrupt collapse of sparsely tethered PSS brushes [26,27]. Our NR results demonstrate that this conclusion also holds for densely tethered PSS brushes.…”
Section: +supporting
confidence: 67%
“…The scattering length density of PSS, ρ p = 2.248×10 -6 /Å 2 , is obtained from the fitting of the X-ray reflectivity data from dry PSSNa films. Both theoretical and experimental work has shown that adding multi-valent counterions can cause an abrupt change in the structure of polyelectrolyte brushes [17,25,27]. We have previously shown that the existence of tri-valent cations (e.g., La 3+ and Ru(NH 3 ) 6…”
Section: Neutron Reflectivity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multivalent counterions can cause dramatic structural changes in polyelectrolyte brushes, because of an entropy‐driven ion‐exchange process and electrostatic crosslinks. Tirrell and co‐workers performed SFA measurements with PSS brushes in solutions that contained different divalent and trivalent counterions at fixed ionic strengths (Figure ) ,,. Compared to monovalent counterions, divalent and trivalent counterions caused rapid collapse of the polyelectrolyte brushes in both the osmotic brush and salted brush regimes,, as indicated by a rapid narrowing in the range of repulsive forces between two PSS brushes that were synthesized using SI‐ATRP .…”
Section: Sfa Measurements On Polyelectrolyte Brushesmentioning
confidence: 99%
“…Tirrell and co‐workers performed SFA measurements with PSS brushes in solutions that contained different divalent and trivalent counterions at fixed ionic strengths (Figure ) ,,. Compared to monovalent counterions, divalent and trivalent counterions caused rapid collapse of the polyelectrolyte brushes in both the osmotic brush and salted brush regimes,, as indicated by a rapid narrowing in the range of repulsive forces between two PSS brushes that were synthesized using SI‐ATRP . Additionally, attractive forces were measured when separating two physisorbed PSS brushes in the presence of trivalent [Ru(NH 3 ) 6 ] 3+ and La 3+ species, but the attractions induced by La 3+ ions were stronger than those caused by [Ru(NH 3 ) 6 ] 3+ complexes, presumably owing to the smaller hydration radius of La 3+ ions.…”
Section: Sfa Measurements On Polyelectrolyte Brushesmentioning
confidence: 99%